A Novel Solid–Solid Phase Change Material: Pentaglycerine/Expanded Graphite Composite PCMs. Issue 10 (25th June 2018) - Zhang, Nan; Song, Yanlin; Du, Yanxia; Yuan, Yanping; Xiao, Guangming; Gui, Yewei
Abstract : In this work, a novel solid–solid phase change material (SS‐PCM), pentaglycerine/expanded graphite (PG/ExG) is developed. ExG is introduced into PG to enhance its thermophysical properties. The results of SEM, FT‐IR, and XRD indicate that PG and ExG are physically well combined in the composites. DSC results show that the phase change temperature of the PG/ExGs are not significantly different from those of PG. The melting latent heat of PG/ExG containing 1, 2, and 4 wt% ExG are 163.8, 161.6, and 160.1 J g −1, respectively. Although the latent heat of PG/ExG decreases with the addition of ExG, the total heat storage capacity of PG/ExG increases due to the increase in specific heat of composite PCMs. The thermal conductivities of PG/ExG containing 1, 2, and 4 wt% ExG are 0.647 W/(m · K), 0.863 W/(m · K), and 0.944 W/(m · K), respectively, while that of PG is just 0.232 W/(m · K). Thermal performance tests further verify the enhancement to heat transfer performance of PG with ExG. The results of thermal cycling tests substantially indicate that the PG‐based SS‐PCMs have noticeable thermal reliabilities after 100 cycles. In conclusion, the PG/ExG composite PCMs with comprehensive properties will have potential for usage in energy storage and thermal management systems. Abstract : A series of SS‐PCMs are prepared by introducing expanded graphite (ExG) into pentaglycerine (PG). PG and ExG are physically combined with each other. The total heat storage density (sensible and latent heat) of PG/ExG composites are not decreased by adding ExG. Thermal conductivity of PG/ExG composites are increased with the increasing of ExG. PG/ExG composites show the excellent thermal properties.